Quantitative determination of the amino acid content of rumen fluid from twin steers fed soybean oil meal or urea - Richardson, D.; Tsien, W.S. (Kansas Agricultural Experiment Station, 2011)
Crude protein, or protein as the term is commonly used, represents all nitrogen-containing compounds in the feed. True protein is that portion of the protein which has been formed by the combining of amino acids. The value of any protein supplement is determined by its amino acid content plus the ability of the animal to synthesize true protein in the digestive tract from non-protein nitrogen sources. The purpose of this test was to determine the amino acid content of rumen fluid of steers fed soybean oil meal or urea.
Keywords: Beef; Amino acid; Soybean oil meal; Urea